2019
DOI: 10.1037/aap0000167
|View full text |Cite
|
Sign up to set email alerts
|

Special issue introduction: Advancing Native Hawaiian and other Pacific Islander health.

Abstract: This is an introductory article for the special issue on “Advancing Native Hawaiian and Other Pacific Islander Health” of the Asian American Journal of Psychology. It provides a demographic and historical overview of Native Hawaiians and other Pacific Islanders in the United States as well as the most pressing physical and mental health issues faced by these communities. In so doing, this article provides the larger cultural and social context for the studies that comprise this special issue. The eight article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…The United States population consists of 1.4 million Native Hawaiian and Pacific Islander (NHPI) individuals (1). NHPI individuals have their origins in one of three main regions located in the Pacific, which include Polynesia (e.g., Samoa), Micronesia (e.g., Guam), and Melanesia (e.g., Fiji) (2). Historically, it has been extraordinarily difficult to assess health and health behavior data specific to the NHPI population because of institutionalized discriminatory policies that did not recognize specific racial and ethnic groups or allow for self‐identification if an individual’s race or ethnicity was not represented as a category.…”
Section: Introductionmentioning
confidence: 99%
“…The United States population consists of 1.4 million Native Hawaiian and Pacific Islander (NHPI) individuals (1). NHPI individuals have their origins in one of three main regions located in the Pacific, which include Polynesia (e.g., Samoa), Micronesia (e.g., Guam), and Melanesia (e.g., Fiji) (2). Historically, it has been extraordinarily difficult to assess health and health behavior data specific to the NHPI population because of institutionalized discriminatory policies that did not recognize specific racial and ethnic groups or allow for self‐identification if an individual’s race or ethnicity was not represented as a category.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we suggest that clinicians familiarize themselves with the extant work of researchers, healthcare providers, and clinicians who have documented important contextual factors and therapy considerations when working with specific groups within this population. We recommend clinicians interested in learning more read any of the following overview articles/books written by Allen and Smith (2015) and Allen et al (2016), Braun et al (2014Braun et al ( , 2015, Culbertson, et al (2007), Kaholokula et al (2012Kaholokula et al ( , 2019, Mau (2010); Marsella et al (2005), Valentine et al (2017), andWhealin et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ACEs increases risk of adverse health outcomes including ischemic heart disease, cancer, obesity, and a myriad of psychosocial problems. Micronesian Islanders and other Asian/Pacific Islanders experience ACEs at rates higher than other ethnic groups (Kaholokula, Okamoto, & Yee, 2019). Although the data were not disaggregated into subgroups, Sieben, Lust, Crose, Renner, and Nguyen (2019) found that Asian/Pacific Islanders were 10% more likely than Whites to witness parental physical abuse and over 8% more likely to be victims of parental physical abuse.…”
Section: Problem/significance Of Topicmentioning
confidence: 92%